Concentration and Determinants of Carbon Dioxide (CO2) Emissions in 25 Asian Countries from 2015 to 2021 - Sugiarto, Dennys Ilham; Hastuti, Sri Rahayu Budi (Soegijapranata Catholic University, 2025)
This study analyzes the concentration of carbon dioxide (CO2) emissions and their determinants in 25 Asian countries from 2015 to 2021. Carbon dioxide (CO2) is a greenhouse gas produced by human activities, such as fossil fuel combustion. The study utilizes secondary data and employs two analytical tools: the concentration index, which identifies countries with the highest CO2 emissions, and panel data regression to analyze its determinants. The findings reveal that 13 out of 25 countries have a concentration index greater than one, with Japan, Russia, and Azerbaijan ranking as the top three countries with the highest CO2 emission concentrations, while Vietnam has the lowest concentration index, with a value of less than one. The variables of oil consumption, natural gas consumption, coal consumption, and population size have a positive and significant effect on CO2 emissions in the 25 Asian countries. On the other hand, economic growth does not have a significant impact on CO2 emissions. These findings highlight the urgency of implementing energy transition policies in high-emission countries as a strategic measure to reduce dependence on fossil fuels. Furthermore, the development of population-based policies oriented toward sustainability is deemed crucial to effectively reducing carbon emissions across the Asian region.